Market mix Affecting Assurance Holder’s The consumer’s Decision to Purchase a House in a Housing Estate in Mueng Districe, Kanchanaburi Province - Khamlek, Manit; Kitiyanan, Sanchai (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
This research aimed to investigate market mix affecting assurance holder ,the consumer, decision to purchase a house estate in mueang districe , kanchanaburi province the objective of this independent study was to study the market mix affecting assurance holder, the consumer, decision to purchase a house estate in mueang districe, kanchanaburi. The study method used was collecting data from questionnaires distributed to 375 samples in mueang The population living in housing. The data was statistically analyzed for summarization using frequency, percentage, and average. The results of the study were as follows. Most of the respondents were women between the ages of 46-55 years. With a bachelor’s degree. A career as a private income during 20,000-25,000 baht Status needs house land 51-70 square in house prices 1,500,000-2,000,000 baht. The results showed that most of the respondents give priority to the location of the project, followed by the promotion of the product respectively. It was also found that the respondents have decision-making behavior in buying house compared house style, price, location of the project promotion project at the highest level followed by Selection of project information and view the properties of a house before you buy. In addition, the study also found that the influence of the marketing mix on the decision to purchase the house allocation of consumers in the urban area of Kanchanaburi including marketing mix, price. Article history : Accepted 7 August 2016 SIMILARITY INDEX = 0.00